Biosilica from diatomaceous earth as support to CdS-mediated photocatalysis in dry and aqueous phase. (5th August 2017) - Nascimento, Cristiane C.; Andrade, George R.S.; Santos, Oseas S.; Neto, Erico Teixeira; Costa, Silvanio S.L.; Gimenez, Iara F.
Abstract: This work reports the use of diatomite biosilica as support to deposition of homogeneously dispersed CdS nanoparticles by aqueous reaction. Time evolution of the process revealed that 30 min are sufficient to obtain well dispersed hexagonal CdS nanoparticles, without formation of external particles. Characterization by UV/visible reflectance spectroscopy allowed estimating nanocrystal size as ranging from 4 to 6 nm, while TEM and STEM images showed that those primary CdS nanocrystals formed aggregates with 14.2–71.8 nm depending on the reaction time. Photocatalysis in flow setup through glass column under solar light, under UVA irradiation and adsorption in dark conditions showed that the process under solar light was the most efficient. Photocatalytic tests in dry phase under solar light revealed that the presence of CdS favors dye degradation when compared to diatomite containing the adsorbed dye. Finally, photocatalysis of aqueous suspensions under solar light was also more efficient than adsorption or photolysis, following pseudo-first order kinetics with a half time of 46.2 min. Graphical abstract: Highlights: Thermolysis of Cd-thiourea complex formed CdS nanoparticles. CdS nanocrystals were deposited onto diatomite biosilica. CdS diameters were 14.2, 44.8 and 71.8 nm respectively after 3.3, 11 and 30 min. Photocatalyst activities were 96.5% and 95% in aqueous and dry phase respectively.